2005
DOI: 10.1097/01.sle.0000183251.58690.94
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Feeding Jejunostomy Technique as Part of Staging Laparoscopy

Abstract: Placement of a feeding jejunostomy tube is indicated for patients who need enteral access but where a gastrostomy is not feasible. This paper presents the technique and results of laparoscopic placement of feeding jejunostomy tubes in patients presenting with esophagogastric cancer. From December 2002 to February 2004, patients diagnosed with esophagogastric cancer with a potentially resectable lesion underwent staging laparoscopy. Laparoscopic feeding jejunostomy was performed on patients who were potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Several studies have demonstrated the efficacy of a jejunostomy tube as a means of nutritional support in patients receiving neoadjuvant treatment [13,20,21]. However, there are potential complications for jejunostomy tube placement in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of a jejunostomy tube as a means of nutritional support in patients receiving neoadjuvant treatment [13,20,21]. However, there are potential complications for jejunostomy tube placement in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques of anchoring the jejunum to the anterior abdominal wall have been described, either in the forms of transfascial sutures (transabdominal sutures [8, 10] or T-fasteners [5, 16]) or intracorporeal sutures [13, 17]. The transabdominal sutures (3–4 in number) are usually placed in a diamond configuration, incorporating the seromuscular layer of the jejunal wall and the anterior abdominal wall [6].…”
Section: Discussionmentioning
confidence: 99%
“…We compared our data and complication with 12 selected series in the literature that report on the outcomes of laparoscopic feeding jejunostomy (Table 2). The rate for conversion to open surgery ranges from 0 to 12.5% [11, 13], minor complications ranges from 5.3 to 32.1% [11, 20], major complications ranges from 0 to 10.7% [10, 11, 21] and mortality ranges from 0 to 11.1% [5]. The reported complications include wound infection [6, 22]; catheter dislodgement [6, 13, 23]; occlusion [13, 23]; pericatheter leak with generalized peritonitis [24]; aspiration pneumonia [22, 24]; small bowel necrosis [23, 25]; small bowel obstruction [13, 22, 23]; pneumatosis intestinalis [23, 26]; abdominal wall infection [13, 23]; fistula [13, 23]; volvulus [23]; and death [23, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Möglicherweise wird hier die Immunzytochemie einen Fortschritt bringen [62]. Ganz sicher wird in Zukunft aber das (palliativ-)therapeutische Potenzial der Laparoskopie im direkten Anschluss an das Staging zunehmend mehr genutzt werden [29,67].…”
Section: > Selektionskriterien Sollen "Trefferhäufigkeit" Der Edl Verunclassified